1999
DOI: 10.1046/j.1439-037x.1999.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Economy, Dry Matter Production and Seed Production Potential of Setaria sphacelata by Intercropping of Pasture Legumes

Abstract: Field experiments were conducted to evaluate the per! formance of _ve pasture legumes "Sesbania sesban\ Desmenthus vir`atus\ Stylosanthes scabra\ Clitoria ternatea\ and Desmodium tortuosum used as intercropped component# with respect to nitrogen economy\ dry mat! ter and seed yield potential of Setaria sphacelata * a grass based management system which was maintained from 0882 to 0884 at Research Farm\ Indian Grassland and Fodder Research Institute\ Jhansi under rainfed con! dition[ Legumes like Clitoria terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Field trials conducted in Mexico reported that at 180 days post planting of C. ternatea , the organic matter, N, P, and K content of the soil all increased significantly (Alderete-Chavez et al, 2011). A similar study conducted in India reported that intercropping C. ternatea with the fodder crop Setaria sphacelata enriched the N content of the soil to an estimated 39.8 kg/ha (Dwivedi and Kumar, 2001). The results suggest that intercropping C. ternatea may potentially lead to a shorter fallow period requirement (Njunie et al, 2004).…”
Section: Historical and Current Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Field trials conducted in Mexico reported that at 180 days post planting of C. ternatea , the organic matter, N, P, and K content of the soil all increased significantly (Alderete-Chavez et al, 2011). A similar study conducted in India reported that intercropping C. ternatea with the fodder crop Setaria sphacelata enriched the N content of the soil to an estimated 39.8 kg/ha (Dwivedi and Kumar, 2001). The results suggest that intercropping C. ternatea may potentially lead to a shorter fallow period requirement (Njunie et al, 2004).…”
Section: Historical and Current Applicationsmentioning
confidence: 93%
“…Supplementing the soil with sulfur was also demonstrated as beneficial for nodule formation (Zaroug and Munns, 1980a). Several studies have reported the benefits of C. ternatea to soil health (De Souza et al, 1996; Dwivedi and Kumar, 2001; Kamh et al, 2002; Alderete-Chavez et al, 2011). Field trials conducted in Mexico reported that at 180 days post planting of C. ternatea , the organic matter, N, P, and K content of the soil all increased significantly (Alderete-Chavez et al, 2011).…”
Section: Historical and Current Applicationsmentioning
confidence: 99%
“…Sudan grass is one of the cereal forages with high yielding ability that gives up to four cuts during the growing season. Forage grasses benefit from the addition of legumes in the intercropping and the productivity may be equal to nitrogen fertilization (Dwivedi and Kumar, 1999). In drought stress experiment Eneji et al (2008) found that Sudan grass, compared with the other three forage plants, was the least affected by deficit irrigation, possibly on account of improved root mass and its natural drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the production per unit area, intercropping systems provide resources to the resource-poor farmers, more efficient use of land and labor, and better control of weeds, insects/pests, and pathogens than sole crops (Singh and Rathi 2003). Intercropping has been in practice for centuries to sustain yield, minimize risk, utilize the lag phase, and improve productivity (Aiyer 1949;Jodha 1977;Willey 1979a;Dwivedi and Kumar 1999;Rao 2000;Sharma and Gupta 2001). Because information is lacking on the influence of integrated nutrient application in chickpea -mustard intercropping system, the present study was undertaken to see if the combined use of organic, inorganic, and biofertilizers under moisture-stress situations could enhance sustainable yield.…”
Section: Introductionmentioning
confidence: 99%